Las acciones afirmativas y las consecuencias de aplicación en los concursos de méritos y oposición en el UNACH, periodo 2015-2018" - Byron Paúl, Llangari Andrade (2021)
ABSTRACT Affirmative action originates from the United States of America, designed to decrease discrimination against specific objects groups of people due to their ethnic or racial origin. This objective has been extended to the rest of the world. Although with much broader content and scope, to be applied in any social relations sector and to different people or groups historically discriminated against or in vulnerability situations. Affirmative action as an anti-discrimination policy was incorporated in Ecuadorinto the 2008 Constitution from there to the rest of the legal system, including concourses for merits and opposition to enter the public sector. The present investigation starts with theoretical and legislative assumptions to develop and analyze the application of affirmative actions in the merits and opposition concourses at UNACH. A documentary investigation has been carried out, with an explanatory and complementary scope with a survey applied to people related to the institution's subject, concluding that its application in short stories has been limited. Consequently, the Honorable University Council of UNACH has to propose in the General Regulations for the Application of Affirmative Actions of the specific rules on its application in competitions that mark an institutional vision according to its particularities and the social context in which it is inserted. Keywords: equality, non-discrimination, affirmative action, UNACH, merits, and opposition concourses.